2020
DOI: 10.3390/ijms21051598
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigen Treatment in Type 1 Diabetes: Unsolved Questions on How to Select Autoantigen and Administration Route

Abstract: Autoantigen treatment has been tried for the prevention of type 1 diabetes (T1D) and to preserve residual beta-cell function in patients with a recent onset of the disease. In experimental animal models, efficacy was good, but was insufficient in human subjects. Besides the possible minor efficacy of peroral insulin in high-risk individuals to prevent T1D, autoantigen prevention trials have failed. Other studies on autoantigen prevention and intervention at diagnosis are ongoing. One problem is to select autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 142 publications
(157 reference statements)
0
21
0
2
Order By: Relevance
“…Autoantigen treatment has been tried in many autoimmune diseases, with poor results. There are several problems to be solved, such as selection of autoantigen, dose, timing, and route of administration ( 32 ). This study confirmed the positive effects of intralymphatic autoantigen treatment, suggested in our previous first-in-human pilot trial ( 19 ), and this route of administration may therefore be of interest for trials in other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantigen treatment has been tried in many autoimmune diseases, with poor results. There are several problems to be solved, such as selection of autoantigen, dose, timing, and route of administration ( 32 ). This study confirmed the positive effects of intralymphatic autoantigen treatment, suggested in our previous first-in-human pilot trial ( 19 ), and this route of administration may therefore be of interest for trials in other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent trial, GAD‐alum was administered subcutaneously in a prime‐boost regimen to children with existing islet autoimmunity in order to prevent disease development but, although well‐tolerated, the primary endpoint was not reached 53 . Interestingly, subsequent analysis of these trials has revealed that GAD‐alum treatment is more efficacious in preserving C‐peptide secretion in patients positive for HLA‐DR3/DQ2—a haplotype associated with GAD65 autoimmunity—than in patients with a DR4/DQ8 genotype 54 …”
Section: Fighting Fire With Fire: Antigen‐specific Interventionsmentioning
confidence: 99%
“…53 Interestingly, subsequent analysis of these trials has revealed that GADalum treatment is more efficacious in preserving Cpeptide secretion in patients positive for HLA-DR3/DQ2 -a haplotype associated with GAD65 autoimmunitythan in patients with a DR4/DQ8 genotype. 54 Recent studies have combined GAD-alum with other immunomodulatory agents. In the DIAGNODE-1 study, patients with newly diagnosed T1D received three lowdose GAD-alum injections directly into an inguinal lymph node and an oral vitD supplement.…”
Section: Fighting Fire With Fire: Antigen-specific Interventionsmentioning
confidence: 99%
“…In some cases, immune suppression may be efficaceous, but it will be difficult to avoid unacceptable adverse events and risks. Auto-antigen treatment may become a safe way forward but we need to know more about the route of administration, doses, what autoantigens to use in different patients [ 49 ]. Furthermore, we will probably need to combine different regimens and agents, in a similar way as been used with great success in, for example, pediatric oncology [ 34 ].…”
Section: Future Perspectivementioning
confidence: 99%